Master of the revels : a return to Neal Stephenson's D.O.D.O. - Galland, Nicole, 1955- (William Morrow, an imprint of HarperCollinsPublishers, 2021)
"In this brilliant sequel to The Rise and Fall of D.O.D.O.--an enthralling, history-bending adventure traversing time and space, fact and fiction, magic and science co-written with #1 New York Times bestselling author Neal Stephenson--a daring young time traveler must return to Jacobean England to save the modern world"--